2015
DOI: 10.1177/2047487315597210
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new method for non-invasive assessment of vasomotor function

Abstract: FMS is a reproducible technique, which is able to detect differences in vasomotor function both in a condition associated with endothelial dysfunction and following an acute intervention known to improve endothelial function. This simple technique has potential for accessible assessment of vasomotor function in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 24 publications
2
36
2
Order By: Relevance
“…For example, one study compared the reliability of brachial FMD to brachial–radial PWV min % in a group of 22 healthy participants (28–65 years old), reporting a coefficient of variation (CV) of 7.3% for PWV min % and 26.6% for FMD. 7 The same study reported a CV of 3.3% for PWV, and, while PWV min was not reported, the CV for the absolute change in PWV (PWV min – baseline PWV) was 8.2%. The reported reliability of FMD and PWV are in accordance with the available literature.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, one study compared the reliability of brachial FMD to brachial–radial PWV min % in a group of 22 healthy participants (28–65 years old), reporting a coefficient of variation (CV) of 7.3% for PWV min % and 26.6% for FMD. 7 The same study reported a CV of 3.3% for PWV, and, while PWV min was not reported, the CV for the absolute change in PWV (PWV min – baseline PWV) was 8.2%. The reported reliability of FMD and PWV are in accordance with the available literature.…”
Section: Discussionmentioning
confidence: 92%
“…PWV min ). As such, while a limited number of studies have reported that PWV min % is reduced in those with cardiovascular complications, 5 7 and that PWV min % is associated with cardiovascular risk factors, 9 these findings may not be attributable to endothelial function. Alternatively, the lack of effect of endothelial dysfunction on PWV min % in the current study may be attributable to a shifting numerator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that a series of regional factors may account for the difference in the FMD reaction in the brachial and femoral arteries 39 and that the shear stress after cycling may significantly increase the diameter of the femoral artery compared with the diameter of the brachial artery, which may account for the observed difference in arterial stiffness and PWV. 40,41 A recent meta-analysis focusing on studies of aerobic exercise concluded that the improvement in the brachial ankle PWV was based mainly on the improvement in the peripheral arterial stiffness and PWV. This was attributed to the greater shear stress enhanced release of nitric oxide in the peripheral exercising limbs and the nitric oxide production in small conduit arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, carotid‐radial PWV was measured at rest and again approximately 60 s postregional circulatory arrest via cuff inflation around the forearm to a suprasystolic pressure for 5 min (Cauwenberghs et al., 2018). Flow‐mediated slowing (FMS) of carotid‐radial PWV postcuff release was used as a measure of peripheral vasomotor function that is partially mediated by endothelial‐dependent vasodilation (Ellins et al., 2016; Nicholas et al., 2018; Pereira, Almeida, & Conde, 2018; Stoner et al., 2020). Ankle brachial index (ABI) was determined to rule out presence of peripheral artery disease (ABI 0.9‐1.4, normal; ABI < 0.9, peripheral artery disease).…”
Section: Methodsmentioning
confidence: 99%